Molecular typing, antibiotic susceptibility, and biofilm production in nonencapsulated Streptococcus pneumoniae isolated from children in Japan. Issue 10 (October 2019) - Takeuchi, Noriko; Ohkusu, Misako; Wada, Noriyuki; Kurosawa, Satoko; Miyabe, Akiko; Yamaguchi, Masashi; Nahm, Moon H.; Ishiwada, Naruhiko
Abstract: The prevalence of nonencapsulated Streptococcus pneumoniae (NESp) has increased with the introduction of pneumococcal conjugate vaccines in children; however, the bacteriological characteristics of NESp have not been sufficiently clarified. In this study, NESp strains isolated from the nasopharyngeal carriage of children from four nursery schools in Japan were analyzed for molecular type, antibiotic susceptibility, and biofilm productivity. A total of 152 putative S. pneumoniae strains were identified by optochin-susceptibility analysis, of which 21 were not serotypeable by slide agglutination, quellung reaction, or multiplex PCR. Among these 21 strains, three were lytA -negative and, therefore, not S. pneumoniae . The remaining 18 strains were positive for lytA, ply, pspK, and bile solubility and were confirmed as NESp. Therefore, the isolation rate of NESp in the S. pneumoniae strains in this study was 12.0% (18/149). Molecular-typing analyses classified five strains as two existing sequence types (STs; ST7502 and ST7786), and 13 strains formed four novel STs. Horizontal spread was suspected, because strains with the same ST were often isolated from the same nursery school. The NESp isolates were generally susceptible to most antimicrobials, with the exception of macrolides; however, all isolates possessed more than one abnormal penicillin-binding protein gene. Furthermore, NESp strains were more effective than encapsulated counterparts at forming biofilms, which showed obvious differences in morphology. These data indicated that NESp strains should be continuously monitored as emerging respiratory pathogens.